Chemical constituents of the leaves of Alnus nepalensis D. Don. (Betulaceae) - Son et al, Phan Tong (Vietnam Journal of Chemistry, 2014)
Taraxeryl acetate (1), physcion (2), 1-nonacosanol (3), b-sitosterol (4), quercetin (5), b-sitosterol 3-O-b-D-glucopyranoside (6), and quercitrin  (7) were isolated from the leaves of Alnus nepalensis D. Don. (Betulaceae). Their structures were determined by spectroscopic methods.